Social Inclusion and Self-Actualization of Individuals with Autism: the Role of a Community Running Program - Ninik Kristyaningsih; Gunarhadi Gunarhadi; Joko Yuwono (Teknodika, 2026)
Individuals with Autism Spectrum Disorder (ASD) face persistent challenges in social interaction and communication, which may hinder their self-actualization. In Indonesia, these challenges are further compounded by limited access to inclusive environments and ongoing social stigma. This study examines the role of a community-based running program as an inclusive space that supports social interaction and self-actualization among individuals with ASD. A qualitative case study approach was employed, involving eight participants, including adults with ASD, parents or caregivers, and community organizers. Data were collected through semi-structured interviews, participatory observation, and document analysis, and analysed using the Miles and Huberman interactive model with triangulation to ensure validity. The findings indicate that participation in the running community contributes to improved social interaction, increased confidence, and greater engagement in meaningful activities. Community organizers play a critical role as social mediators, facilitating inclusion and supporting interaction between individuals with ASD and the broader community. The study also proposes a step-by-step model for developing inclusive running programs and highlights the potential of community-based approaches as cost-effective complements to clinical intervention. These findings suggest that inclusive social communities can serve as sustainable and replicable platforms for supporting the self-actualization of individuals with ASD in naturalistic settings.